2020
DOI: 10.1016/j.ihj.2020.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hypertension subtypes in a hill tribe of Mizoram, Northeast India

Abstract: Objective Hypertension is a potential risk factor for cardiovascular diseases. With increasing age there is differential rise of systolic and diastolic blood pressure leading to development of various hypertension subtypes which have its own clinical implications. Present study assessed distribution and risk factors of hypertensive subtypes in the hill tribe of Mizoram. Methods The present study was a community-based cross-sectional study carried out in Aizawl, Mizoram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Despite the diversity in dietary habits and cultural practices, studies on diabetes and hypertension in Northeast India have not, to our knowledge, investigated the geographical heterogeneity in the causes of diabetes and hypertension [ 22 , 23 ]. According to Koissi et al, overlooking the effects of heterogeneity in the statistical model may lead to biased parameter estimates [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the diversity in dietary habits and cultural practices, studies on diabetes and hypertension in Northeast India have not, to our knowledge, investigated the geographical heterogeneity in the causes of diabetes and hypertension [ 22 , 23 ]. According to Koissi et al, overlooking the effects of heterogeneity in the statistical model may lead to biased parameter estimates [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The odds of HTN was more among 36–49 years women, women with overweight/obesity and those using additional salt, which is similar to other studies. 15 , 16 , 26 Chakma et al observed 1.5 times higher odds of hypertension among those using table salt. 22 …”
Section: Discussionmentioning
confidence: 98%
“…15 Study carried out by Borah et al among Hill tribe of Mizoram reported 12% prevalence of HTN (JNC 7 criteria) which is similar to our study. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Study carried out by Borah et al among hill tribe of Mizoram reported 12% prevalence of hypertension. 19 In a study conducted in Manipur, overweight and obese were 7.39 times more likely to have stage II hypertension. 20 As per NFHS -5, 22.2% of women in Kamrup District (Rural) were found to be having elevated blood pressure (systolic ≥140 mm of Hg and diastolic ≥90 mm of Hg) 21 .…”
Section: Introductionmentioning
confidence: 99%